Energy flexibility assessment of a zero-energy office building with building thermal mass in short-term demand-side management. (1st June 2022) - Lu, Fei; Yu, Zhenyu; Zou, Yu; Yang, Xudong
Abstract: Zero-energy buildings (ZEBs) play an increasingly important role in energy networks. Owing to the uncertainty of renewable energy generation, the focus on ZEBs should not only be on the annual zero balance but also on utilizing energy flexibility to alleviate the real-time energy imbalance. In this study, a generic simulation-based methodology was developed to evaluate the energy flexibility of ZEBs. Quantitative indicators that consider the flexibility potential and influence of flexible activation were proposed. The methodology was applied to a zero-energy office building in Beijing, China. The short-term flexibility of the building thermal mass under different boundary conditions and flexible events was evaluated. The results showed that under the benchmark scenario, the average energy reduction was 8.13 Wh/m 2 for the occupied hours, and average energy increase was 23.53 Wh/m 2 for the off-peak period and 4.7 Wh/m 2 for the surplus generation period. The ZEB has considerable flexibility in responding to the energy supply side. However, boundary conditions and event start times affect the flexibility performance. The influence of different flexible events on the supply side is diverse and may be negative. Appropriate events should be implemented based on the results to avoid adverse effects on the energy supply side. Highlights: A quantitative method for energy flexibility of zero-energy buildings is proposed. Short-term energy flexibility of a zero-energy office building in China is studied. Energy flexibility of building thermal mass is considerable but diverse. The impact of flexibility activation on the energy supply side may be negative. Boundary conditions and event start times affect the flexibility performance.